2000
DOI: 10.1093/treephys/20.11.745
|View full text |Cite
|
Sign up to set email alerts
|

Estimating CO2 flux from snowpacks at three sites in the Rocky Mountains

Abstract: Soil surface CO(2) flux (F(s)) is the dominant respiratory flux in many temperate forest ecosystems. Snowpacks increase this dominance by insulating the soil against the low temperature to which aboveground components are exposed. However, measurement of F(s) in winter may be impeded by snow cover. Likewise, developing annual F(s) models is complicated by seasonal variation in root and microbial metabolism. We compared three methods of measuring sub-snow F(s): (1) dynamic chamber measurements at the upper snow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
91
4
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 26 publications
13
91
4
1
Order By: Relevance
“…It influences both plant phenology [Galen and Stanton, 1995;Ouerbauer et al, 1998;Van Wijk et al, 2003;Dye and Tucker, 2003;Grippa et al, 2005a] and the carbon cycle via the increased ecosystem respiration after melting [Goulden et al, 1998;Chapin et al, 2000;Frauenfeld et al, 2004]. Moreover, snow also plays a role in maintaining carbon fluxes during the winter through its insulating effect on soil temperatures [McDowell et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…It influences both plant phenology [Galen and Stanton, 1995;Ouerbauer et al, 1998;Van Wijk et al, 2003;Dye and Tucker, 2003;Grippa et al, 2005a] and the carbon cycle via the increased ecosystem respiration after melting [Goulden et al, 1998;Chapin et al, 2000;Frauenfeld et al, 2004]. Moreover, snow also plays a role in maintaining carbon fluxes during the winter through its insulating effect on soil temperatures [McDowell et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary measurements and leak checking with elevated CO 2 showed that this ventilation hole did not permit entry of external air. The difficulty of accessing the site over winter necessitated use of a smaller more portable system, in our case a LI-8100 (Li-Cor Inc., Lincoln, Nebraska, U.S.A.) with a 20-cm-diameter chamber and 'snowshoe' to allow measurement of CO 2 efflux directly from the snow surface (McDowell et al, 2000). The 20-cm-diameter chamber of the LI-8100 chamber has pressure vents to prevent pressure gradients.…”
Section: Measurement Of Ecosystem Respirationmentioning
confidence: 99%
“…From measurements in ecosystems with colder and longer winters there is substantial evidence that respiration continues beneath snow and this may be a significant contributor to annual C balance (Sommerfeld et al, 1993;Monson et al, 2006aMonson et al, , 2006bLarsen et al, 2007). Measured instantaneous rates of CO 2 efflux for snow-covered ecosystems have been as slow as 0.02 mmol CO 2 m 22 s 21 in an arctic tundra (Jones et al, 1999) to much faster rates of 0.71-0.86 mmol CO 2 m 22 s 21 in a subalpine meadow (Liptzin et al, 2009) and 0.77 mmol CO 2 m 22 s 21 in a temperate conifer forest (McDowell et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emissões em clima temperado são maiores no verão do que no inverno, independentemente do tipo de cobertura vegetal. [15][16][17] A quantificação das emissões de CO 2 também é tema relevante, e a busca por equipamentos de baixo custo e de fácil manuseio em campo tem sido constante. Dentre os métodos empregados, o da câ-mara dinâmica determina o fluxo de CO 2 emitido baseado na variação de concentração dos gases emitidos pelo solo no interior da câmara, 18 com determinação direta das concentrações por analisadores de gás infravermelho, também conhecido como IRGAS, do inglês, Infra Red Gas Analiser.…”
Section: Introductionunclassified